The influence of profitability, company size, and the audit committee on earnings quality - Magdalena, Annastasia; Rahmiati, Rahmiati; Diarsyad, M. Ichsan (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2024)
This study aims to provide an empirical explanation of the effect of profitability, company size and audit committee on earnings quality. This study uses quantitative descriptive research with secondary data in the form of annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sample selection used purposive sampling, and the number of samples used was 115 samples, and the analysis tool used was Statistical Product and Service Solutions (SPSS) 26. The analysis techniques used are descriptive analysis and multiple linear regression analysis. The results of the research indicate that profitability has no effect on earnings quality; 2) company size has no effect on earnings quality; 3) audit committee has a positive and significant effect on earnings quality; and 4) profitability, company size and audit committee simultaneously affect earnings quality.